Perancangan Rumah Ramah Lingkungan Di Desa Kertawangunan, Kuningan, Jawa Barat - Dini Prianingsih; Dadang Sujana; Hafiz Abdillah (JURNAL ILMIAH FAKULTAS TEKNIK, 2023)
Kertawangunan Town, Kuningan, West Java is a region that has a great deal of green open land as rice fields and ranches. The land can be utilized for harmless to the ecosystem structures like houses. The plan of harmless to the ecosystem private houses is planned by considering parts of existing site conditions, sun powered dissemination, wind development, and other natural perspectives to address private issues for warm solace. To accomplish that should be possible with the technique for normal ventilation and regular lighting. From the consequences of the review it was observed that the best structure direction is pointing toward the east-west, toward this path the sun sparkles the entire day. On the off chance that the light power is high, vegetation can be established nearby around the structure with obscure and cooling tree species. It can likewise give an option in contrast to the structure, like making wooden sheets toward the sun to lessen brightness and expand openings to course air from outside the room. To give regular coolness to the structure, a distance is made between the structure and the current one so the breeze can move uninhibitedly in the room. Keywords : Daylighting, desain and natural ventilation